The Pathogenicity of BPI-ANCA in a Patient With Systemic Vasculitis - Takeda, Sayo; Watanabe-Kusunoki, Kanako; Nakazawa, Daigo; Kusunoki, Yoshihiro; Nishio, Saori; Atsumi, Tatsuya (Frontiers in Immunology, 2019)
OBJECTIVE: ANCA associated vasculitis (AAV) is characterized by systemic necrotizing vasculitis with the presence of ANCA. Although BPI-ANCA is one of the atypical ANCAs and is occasionally seen in patients with vasculitis, the pathogenicity of BPI-ANCA remains unclear. This study was performed to examine the pathogenic role of BPI-ANCA against neutrophils. METHODS: A 76-year-old Japanese man showed BPI-ANCA positive systemic vasculitis with a medical history of Pseudomonas aeruginosa infection. BPI-ANCA IgGs were eluted from the patient serum using an immunoadsorbent column. In vitro experiment, healthy donor neutrophils were treated with BPI-AAV IgGs, MPO-AAV IgGs, healthy control IgGs under TNFα stimulation. After 3 hours incubation, neutrophil extracellular trap (NET) was assessed by immunofluorescent imaging. To determine the pathogenicity of BPI-ANCA, TNFα-primed neutrophils were incubated with monoclonal BPI-ANCA in the presence or absence of recombinant BPI. RESULTS: BPI-AAV IgGs-treated neutrophils showed NET formation with histone citrullination. Interestingly, the monoclonal BPI-ANCA did not induce NET, but the immune complexes (ICs) of recombinant BPI and BPI-ANCA induced TNFα-dependent NET formation with hypercitrullination. Furthermore, TNFα increased the expression of BPIs in neutrophils and the BPIs were translocated to cell surface. CONCLUSION: BPI-ANCA could affect neutrophils leading to NET formation and may play a role in the development of systemic vasculitis as pathogenic autoantibody.